Therapeutically Fine-Tuning Autonomic Nervous System to Treat Sepsis: A New Perspective on the Immunomodulatory Effects of Acupuncture - Zhang Z; Zhang D; Lin Q; Cui X (Dove Medical Press, 2024)
Ziyi Zhang,1 Dingdan Zhang,1 Qing Lin,2 Xiang Cui1 1Department of Physiology, Institute of Acupuncture and Moxibustion, China Academy of Chinese Medical Sciences, Beijing, 100700, People's Republic of China; 2Department of Anesthesiology and Critical Care Medicine, Johns Hopkins University, School of Medicine, Baltimore, MD, 21287, USACorrespondence: Qing Lin, Department of Anesthesiology & Critical Care Medicine, Johns Hopkins University, School of Medicine, Baltimore, MD, 21287, USA, Tel +1-4432072315, Email qlin2@jhmi.edu Xiang Cui, Department of Physiology, Institute of Acupuncture and Moxibustion, China Academy of Chinese Medical Sciences, Beijing, 100700, People's Republic of China, Tel + 86-10-64089422, Email drcuixiang@163.comAbstract: Recent studies have highlighted the immunomodulatory effects of acupuncture on sepsis and proposed novel non-pharmacological or bioelectronic approaches to managing inflammatory illnesses. Establishing rules for selectively activating sympathetic or vagal nerve-mediated anti-inflammatory pathways using acupuncture has valuable clinical applications. Over the years, studies have revealed the segmental modulatory role of acupuncture in regulating visceral function by targeting the autonomic nervous system (ANS). In this review, we aim to summarize recent findings on acupuncture in treating sepsis, focusing on the underlying ANS mechanism, as well as the rules of acupoint specificity, intensity, frequency, and other parameters utilized in these studies. Mechanistically, the immunomodulatory properties of the sympathetic nervous system have been highlighted. Furthermore, we explore the immunotherapeutic benefits of acupuncture in treating sepsis. A better understanding of the immunoregulatory mechanism of sympathetic nervous system may offer novel approaches for the development of therapeutics to treat or prevent a variety of inflammatory diseases.Keywords: inflammation, peripheral nerve stimulation, sympathetic nervous system, sympathoadrenal axis, macrophage, bioelectronic medicine